PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA WARUNG GUBRAK KEPRI MALL KOTA BATAM - Firdiyansyah, Indra (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2017)
This study aims to analyze how much influence the quality of service, price and location to customer satisfaction. Sampling method used is Accidental Sampling Method. Samples in this study 100 people from customers Warung Gubrak Kepri Mall Batam and then analyzed the data obtained by using data analysis in quantitative and qualitative. Quantitative analysis includes validity and reliability test, classic assumption test, multiple regression analysis, hypothesis testing through T test and F test, and coefficient of determination analysis (R2). Qualitative analysis is the interpretation of the data obtained in the research and the results of data processing that has been implemented by giving explanations and explanations. Data that has met the validity test, reliability test and classical assumption test is processed so as to produce the following regression equation: Y = 0,398X1 + 0,359X2 + 0,249X3. Hypothesis testing using t test showed that the three independent variables studied proved to significantly influence partially to the dependent variable Customer Satisfaction. Then through the F test can be seen that the three independent variables studied simultaneously affect the dependent variable Customer Satisfaction. Adjusted R Square number of 0.584 indicates that 58.4 percent of Customer Satisfaction variables can be explained by the three independent variables in the regression equation. While the rest of 41.6 percent explained by other variables outside the three variables used in this study.